THE INFLUENCE OF THE TAGLINE “FREE SHIPPING”, FLASH SALE AND SOCIO-ECONOMIC STATUS OF PARENTS ON CONSUMPTIVE BEHAVIOR IN SHOPEE E-COMMERCE ON SHARIA ECONOMICS STUDENTS IN PALEMBANG CITY UNIVERSITIES THROUGH HEDONIC SHOPPING MOTIVATION AS AN INTERVENING VARIABLE - Iffatur Rohmah; Rina Antasari; Deky Anwar (Journal of Economics and Development, 2025)
This study aims to analyze the influence of the "Free Shipping" tagline, flash sales, and parental socioeconomic status on the consumptive behavior of Islamic Economics students at universities in Palembang City, with hedonic shopping motivation as an intervening variable. The research method employed is a quantitative approach, with data analyzed using the SmartPLS application. The population consists of Islamic Economics students at UIN Raden Fatah Palembang, STEBIS IGM, and Muhammadiyah University of Palembang. The results indicate that the "Free Shipping" tagline, flash sales, and parental socioeconomic status partially and simultaneously influence consumptive behavior. Hedonic shopping motivation is proven to be a significant intervening variable that strengthens the relationship between these factors and consumptive behavior. These findings demonstrate that e-commerce promotional strategies and family socioeconomic backgrounds play an important role in encouraging students' consumption patterns. This research offers practical implications for managing student consumption behavior to align with Islamic economic principles. Keywords: Free Shipping, Flash Sale, Socioeconomic Status, Hedonic Shopping Motivation, Consumptive Behavior